DIGITAL ZAKAT IN THE DYNAMICS OF NATIONAL ZAKAT FUND COLLECTION IN INDONESIA - Putra, Riyan; Habibi, Ahmad; Iqbal Fasa, Muhammad (Journal of Management and Islamic Finance, 2025)
The rapid expansion of digital payment systems in Indonesia has transformed the way Muslims fulfil their zakat obligations. This transformation raises an important question regarding the extent to which the growth of digital zakat contributes to national zakat fundraising performance. This study examines the relationship between digital zakat collection and total national zakat fundraising using secondary data from the annual reports of BAZNAS during the period 2019–2024. A descriptive–associative quantitative approach was employed to map year-to-year developments and to test whether the rise in digital zakat corresponds with the upward trend in national zakat receipts. The findings reveal a consistent increase in digital zakat collection accompanied by steady growth in total national zakat fundraising. Regression analysis indicates a statistically significant positive association between both variables, suggesting that digitalization has enhanced accessibility, accelerated payment processes, and broadened the muzakki base. These results underscore the strategic importance of strengthening digital governance, technological infrastructure, and institutional readiness within zakat organizations. The study contributes to the growing discourse on Islamic social finance by providing empirical evidence on the macro-level effect of digital fundraising within Indonesia’s zakat ecosystem